Development and Verification of a Pedagogical Content Knowledge of Physical Education Scale for Republic of Korea Teachers - et. al., Hohyun, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to explore the structure of Pedagogical Content Knowledge of Physical Education (PCK-PE), develop a scale, and verify its validity. This study was divided into primary and secondary preliminary surveys and one main survey. First, a scale was developed through the Delphi verification process after data were collected through an open questionnaire administered to 97 physical education teachers in January 2020. Second, a descriptive statistical analysis and an exploratory factor analysis was performed on data collected from 163 physical education teachers in February 2020. Finally, a questionnaire was administered to 265 physical education teachers in March 2020. The reliability of the scale was analyzed. Through confirmatory factor analysis, convergent, nomological, and discriminant validity were verified. A correlation analysis was conducted to verify criterion-related validity. Based upon the analysis, a PCK-PE scale was developed with 21 questions and five factors: knowledge of curriculum, pedagogy, educational philosophy, education evaluation, and class environment. The reliability and validity of the developed scale were verified.